Sleep Quality and Attentional Function in Adolescent Gamers Aged 13-14 Years in Makassar - Limbeng, Deni Hansen; Wuysang, Audry Devisanty; Gunawan, David; Hamid, Firdaus; Basir, Hasmawaty; Amran, Muhammad Yunus (Sarana Ilmu Indonesia (salnesia), 2024)
The prevalence of adolescents who spend >5 hours per day playing games has a higher risk of developing sleep disorders. Gaming addiction can cause sleep deprivation and the inability to concentrate, which can lead to attention disorders and impulsive behavior. This study is an analytical observational study with a cross-sectional design that aims to determine the relationship of sleep quality in adolescent gamers to impaired attentional function at SMP Negeri 30 Makassar which was conducted in January 2023. The total subject in the study was 64 people. Most of the subject had a duration of playing games of 3-6 hours per day, which totaled 35 (54,6%) people. Gamers who have abnormal sleep quality are 43 (67,2%). We found that the longer duration of gaming caused the sleep quality to decrease (p-value=0,032). There was a significant relationship between the Pittsburgh Sleep Quality Index (PSQI) score with the visual attention test score (p-value=0,001) and the digit span word test score (p-value=0,006). This study concludes that poor sleep quality is associated with impaired attentional function in the accuracy and reaction domain and impaired attentional function in the working memory domain.